Chemically modified palm kernel shell biochar for the removal of heavy metals from aqueous solution - Imran-Shaukat, M; Wahi, R; Rosli, N R; Aziz, S M A; Ngaini, Z (IOP conference series. Earth and environmental science, 2021)
Heavy metals eradication from water is a complicated subject, therefore a viable, resilient, and green technology is imperative. Heavy metal removal can be accomplished through easy access, economical, and efficient sorbents derived from agricultural waste. In the current study, palm kernel shell (PKS) waste was converted into biochar (PKSC) via pyrolysis. Chemical modification was performed on PKSC via acid-base treatment to refine its adsorption properties. Batch experiments were conducted to study the efficiency of PKSC and acid-base treated PKSC (MPKSC) for removal of Cr(IV), Ni(II) and Cu(II). The surface area was increased from 112.934 m 2 /g to 149.670 m 2 /g by acid-based treatment. Batch adsorption study showed that the MPKSC afforded high removal efficiency for Cu (99.29%), Ni (96.77%) and Cr (42.97%). The Cr(IV) and Ni(II) adsorption by PKSC, as well as Cr(IV), Ni(II) and Cu(II) adsorption by MPKSC were best represented by Freundlich isotherm. However, Cu(II) adsorption by PKSC can explained by using Langmuir isotherm. All studied heavy metals fitted the pseudo-second-order kinetic.